2023
DOI: 10.26444/aaem/159649
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with oncological care during the virus pandemic – SARS-CoV-2 taking into account social and demographic factors

Abstract: Introduction and Objective.The aim of the study was to examine the perception of medical services by oncological patients during the pandemic, identifying the key factors influencing it. The assessment of patient satisfaction with the treatment and care provided by doctors and other hospital staff provides important information on the quality of health services. Materials and method. The study involved 394 patients diagnosed with cancer treated as inpatients in five oncology departments. The diagnostic survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Similar to our findings, two other studies reported high levels of patient satisfaction with the overall care and services provided during the pandemic. 77,78 Literature also documents that interprofessional collaboration is associated with higher patient satisfaction. For instance, a team that collaborates effectively connects different specialized care tasks and works together to make joint clinical decisions centered on patient needs and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, two other studies reported high levels of patient satisfaction with the overall care and services provided during the pandemic. 77,78 Literature also documents that interprofessional collaboration is associated with higher patient satisfaction. For instance, a team that collaborates effectively connects different specialized care tasks and works together to make joint clinical decisions centered on patient needs and preferences.…”
Section: Discussionmentioning
confidence: 99%